2014
DOI: 10.1038/srep06591
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of cancer subtype associated long non-coding RNAs and their clinical implications

Abstract: Long non-coding RNAs (lncRNAs) are a kind of RNAs with regulation that participate fundamental cellular processes via diverse mechanisms. Despite the potential importance of lncRNAs in multiple kinds of cancer has been well studied, no comprehensive survey of cancer subtype associated lncRNAs. Here, we performed an array-based transcriptional survey of lncRNAs across 150 lung cancer samples comprising both adenocarcinoma and squamous cell carcinoma, and 306 breast cancer patients with clear clinical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 35 publications
4
100
0
Order By: Relevance
“…For instance, patients with LAD and LSCC differ in clinical outcomes. Zhao et al identified 72 differentially-expressed (23 upregulated and 49 downregulated) lncRNAs in patients with LADs and LSCCs by using human Affymetrix microarrays (HGU133plus2.0) [90]. Likewise, White et al identified 27 lung cancer-associated lncRNAs, which could be used as novel biomarkers for stratifying LADs and LSCCs [91].…”
Section: Lncrnas As Biomarkers Of Nsclcsmentioning
confidence: 99%
“…For instance, patients with LAD and LSCC differ in clinical outcomes. Zhao et al identified 72 differentially-expressed (23 upregulated and 49 downregulated) lncRNAs in patients with LADs and LSCCs by using human Affymetrix microarrays (HGU133plus2.0) [90]. Likewise, White et al identified 27 lung cancer-associated lncRNAs, which could be used as novel biomarkers for stratifying LADs and LSCCs [91].…”
Section: Lncrnas As Biomarkers Of Nsclcsmentioning
confidence: 99%
“…It was reported that SFTA1P was downregulated in NSCC and its main function was lying on epidermal growth, cell attachment and response to DNA damage. 25 The other IncRNA, CASC2, was reported to be inhibited by miR-21 in gliomas and, 26,27 which could be the ceRNA of other oncogenes.…”
Section: Co-expression Of Deis and Tsg Or Oncogenesmentioning
confidence: 99%
“…There is growing evidence that cancer subtype could be characterized by differentiated lncRNA expression pattern, suggesting the potential of lncRNAs as potent biomarkers in cancer subtype. Several studies have observed subtype-specific lncRNA expression pattern between lung adenocarcinoma and squamous cell carcinoma [18, 19]. In breast cancer, the correlation between lncRNA expression and tumor subtype has also been investigated and some subtype-specific lncRNAs were identified [1921].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have observed subtype-specific lncRNA expression pattern between lung adenocarcinoma and squamous cell carcinoma [18, 19]. In breast cancer, the correlation between lncRNA expression and tumor subtype has also been investigated and some subtype-specific lncRNAs were identified [1921]. For example, a well-known lncRNA HOTAIR was up-regulated in the HER2-enriched subgroup [20].…”
Section: Introductionmentioning
confidence: 99%